The United Nations convention on contracts for the International Carriage of Goods Wholly or Partly by Sea an appraisal of the "Rotterdam Rules" - Güner-Özbek, Meltem Deniz; SpringerLink (Online Service). (Heidelberg, Germany Springer Berlin, 2011)
The international carriage of goods by sea has been regulated by international conventions. These include the 'International Convention for the Unification of Certain Rules of Law relating to Bills of Lading' ('Hague Rules'); the ?Protocol to Amend the International Convention for the Unification of Certain Rules of Law Relating to Bills of Lading? ('Visby Rules'); and the 'UN Convention on the Carriage of Goods by Sea.' They were adopted in 1924, 1968 and 1978 respectively and the transport industry's commercial needs have since substantially changed. Furthermore the advent of subsequent regimes has resulted in the uniformity in the carriage of goods by sea once provided by the Hague Rules being lost. In order to update and modernize existing regimes the 'UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea' ('Rotterdam Rules') was adopted on December 11, 2008 by the UN General Assembly and opened for signature on September 23, 2009. Since then drafters of the Rotterdam Rules, academics and practitioners have been publicizing, discussing, and evaluating the Rules. This book is an effort to further explore those same goals
Preface--1 The history of the Rotterdam rules--2 General principles of transport law and the Rotterdam rules--3 The scope of application of the Rotterdam rules and freedom of contract--4 Extended scope of the Rotterdam rules: maritime plus and conflict of the extension with the extensions of other transport law convention--5 Rotterdam rules - Liabilities and obligations of the carrier--6 Construction problems in the Rotterdam rules regarding the identity of the carrier--7 Compensation for damage--8 Obligations and liabilities of the shipper--9 Transport documents in the light of the Rotterdam rules--10 Jurisdiction and arbitration under Rotterdam rules
Electronic reproduction.
Keywords: Rotterdam Rules -- (2008 December 11).; Freight and freightage; Carriers -- Law and legislation; Contracts, Maritime; Delivery of goods (Law)